Immunization Rejection as a Parental Right and Children's Right to Health in the Perspective of Health Law in Indonesia - Witri, Repelita; Putra, Marsudi Dedi (Civiliza Publishing, 2025)
Parental refusal of immunization for children creates a conflict between parental rights in caregiving and the child’s right to health, which is guaranteed by law. This research aims to analyze the conflict between these two rights within the framework of Indonesian health law and to explain the state's authority to protect children's health rights. This research uses a normative juridical method by analyzing legal regulations, scholarly literature, and legal principles concerning the best interests of the child. The results indicate that parental rights are relative and may be restricted if they endanger the child's health. The state has a constitutional obligation to ensure immunization as part of the child’s right to health. The best interests of the child principle form the legal basis for limiting parental rights, and refusal of immunization can be classified as neglect of the child’s rights. This study recommends strengthening immunization regulations, community education, and inter-institutional collaboration between health and legal sectors to ensure optimal protection of children's rights.